A cephalometric treatment evaluation of non-growing openbite cases treated with MEAW therapy - Lim, Diana Dorothy A.
The purpose of this study was to determine the dental, skeletal and soft tissue treatment effects of MEAW treated anterior openbite cases. The pre-treatment (T1) and immediate post-treatmet (T2) cephalographs of 26 non-growing openbite patients were collected for cephalometric evaluation. There was a significant increase in overbite during treatment. No significant change occurred in any of the skeletal measurements. The upper occlusal plane showed a significant amount of anterior downward movement while the lower occlusal plane moved up anteriorly with the bisected occlusal plane remaining constant. There was extrusion of both upper and lower incisors. The upper and lower molars tipped distally with the upper molars showing a significant amount of intrusion. The upper incisors tipped lingually, decreasing the amount of overjet and accounts for the significant amount of retraction of the upper lip. Ten out of the 26 patients had 2-years post-treatment follow-up cephalographs (T3). These were used to evaluate the stability status. Results show no significant change during the post-treatment interval. One out of ten or 10of the sample showed an openbite relapsed at T3. These findings suggest that the MEAW technique is an effective method for treating anterior openbite cases and offers a good chance of maintaining this correction after orthodontic treatment has been completed. The increased stability may be due to molar uprighting and intrusion.